СУТОЧНАЯ ДИНАМИКА СОДЕРЖАНИЯ АТФ В ПИКО- И НАНОПЛАНТОНЕ ОТКРЫТЫХ ВОД ТРОПИЧЕСКОЙ АТЛАНТИКИ - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 1999)
Приведены данные по суточной динамике АТФ пико- и нанопланктона в опытах in situ на дрейфовых станциях и в пробах, отобранных в открытых районах Атлантики, с применением нестандартных методов исследования. Даны количественые характеристики АТФ пикопланктона в слоях с минимальным и максимальным содержанием хлорофилла "а"; исследован характер суточных изменений АТФ пико- и нанопланктона на стандартных горизонтах в 100-метровом слое. Выявлены периодические колебания АТФ в пико- и нанопланктоне, имеющие внутрисуточный масштаб.
Dayly dynamics of ATP content in pico- and nanoplankton of open waters of the Tropical Atlantic
The paper gives data on daily dynamics of ATP content in pico- and nanoplankton which were obtained in in situ experiments conducted at the drift stations and during research cruises to the tropical Atlantic Ocean. The study implied employment of non-traditional research methods. Quanfitative characteristics of the picoplankton ATP from depths with minimum and maximum chlorophill "a" content are given. The character of daily variations of ATP content in pico- and nanoplankton from a standard series of depths within a 0-100 m water column was defined. Periodic fluctuations of pico- and nanoplankton ATP content which took place during a day (24 h) were found.